Controlling charge-transfer properties through a microwave-assisted mono- or bis-annulation of dialkynyl-N-(het)arylpyrroles. Issue 40 (3rd October 2017) - Pierrat, Philippe; Hesse, Stéphanie; Cebrián, Cristina; Gros, Philippe C.
Abstract : Charge-transfer properties dependence on mono or bisannulation of dialkynyl- N -(het)arylpyrroles is reported. Abstract : A selective microwave-assisted mono- and bis-annulation of dialkynyl- N -(het)arylpyrrole derivatives is described. These polycyclic aromatic hydrocarbons (PAHs) have been photophysically and computationally characterized. The mono-annulated systems display interesting charge-transfer properties. By contrast, these properties vanish within the more conjugated bis-annulated compounds.